Copper-Catalyzed Allylation of Amines with Cyclopropyldiphenylsulfonium Trifluoromethanesulfonate - Ma, Yu; Tian, Ze-Yu; Zheng, Shuang-Yang; Zhang, Cheng-Pan (Synthesis, 2022)
Cyclopropyldiphenylsulfonium salt, a famous ylide precursor previously extensively employed in the preparation of cyclic compounds, has been successfully utilized as an efficient allylation reagent in this work. The copper-catalyzed reactions of cyclopropyldiphenylsulfonium trifluoromethanesulfonate with amines in the presence of an appropriate ligand provided the N-allylated products in good yields. Aliphatic/aromatic amines and primary/secondary amines were all converted under mild reaction conditions. This protocol was also applicable to N-functionalization of drug molecules, supplying the corresponding N-allylated compounds in satisfactory yields. The reaction, which showed good functional group tolerance with a wide range of substrates and excellent chemoselectivity, offers an interesting method for the synthesis of N-allyl amines.
Keywords: sulfonium salts; amines; copper; allylation; catalysis